Characterization of changing trends of baseline and future predicted precipitation and temperature of Tigray, Ethiopia - HAFTU ABRHA; HAFTOM HAGOS (Journal of Agrometeorology, 2022)
Precipitation and temperature data of Tigray region of Ethiopia for baseline (1950-2000), future climate projection for mid-century (2050) and end-century (2070) based on medium emission scenario (RCP 4.5) and high emission scenario (RCP 8.5) were obtained from climate model ensembles, Coupled Model Intercomparison Project 5 (CMIP5). Arc GIS 10.1 and Diva GIS 7.5.0 was used for mapping climatic variables and area coverage. Area coverage were computed based on number of cell (1km2). The result indicted that precipitation of the study might be increased 308-1054 mm to 301-1236 mm under both scenario compared with baseline. Temperature of the study area might be increased from 8.1-29 to 11.3-32.4ºC. The area coverage is decreasing at 8.1-16.2 and 16.2-24.3ºC temperature classes at both time slices and RCPs. In the 24.3-32.4ºC the area might be increased at both time slices and RCPs compared with the baseline. In addition, the area coverage for 301-612mm precipitation class might be increased but decreased at 612-924mm at both RCPs and time slices. The area coverage for 924-1236mm class increased at both time slices and RCPs compared with the baseline. Overall, amount of precipitation and temperature might increase at both time slices and RCPs.